Strengthening Occupational Health and Safety Knowledge among Mineral Water Delivery Drivers - Alpinia Shinta Pondagitan; Asterlita Ryane Wenas; Crifianny Praysilia Wenas; Emmanuela Ranita Molenaar; Firmita Dwiseli; Florianus Hans Matheus Mawo; Lady Galatia Lapian; Liang Kevin Arsastha; M Fadhel Nurmidin; Yolanda Anastasia Sihombing (International Journal of Community Service Implementation, 2025)
Mineral water delivery drivers face various occupational risks, including fatigue, accidents, and musculoskeletal disorders due to long working hours and repetitive tasks. However, awareness of Occupational Safety and Health (OSH) in this informal sector remains low. This community service program aimed to improve drivers’ knowledge and awareness of OSH through interactive education, demonstrations, and ergonomic simulations. The activity involved 33 drivers and included a pre-test and post-test to assess knowledge improvement in four areas: risk awareness, PPE usage, ergonomic practices, and general OSH concepts. Results showed a significant increase in average scores—from 53.2 (pre-test) to 79.2 (post-test), with a gain of 26 points.The program proved effective in enhancing OSH understanding among participants. By using participatory and practical approaches, the initiative successfully raised awareness of workplace safety and encouraged safer work behavior. This effort highlights the importance of extending OSH education to informal workers to support a safer and healthier work environment